STRATEGI PERENCANAAN PENGEMBANGANOBYEK PARIWISATA KOTA PROBOLINGGO ( Studi Kasus Pada Taman Wisata Studi Lingkungan Kota Probolinggo ) - Astuti, Veronica Sri; Maksin, Mastina; Maharani Putri, Vero (Universitas Jabal Ghafur, 2025)
This study aims to analyze the development planning strategy of the Environmental Study Tourism Park (TWSL) in Probolinggo City using six indicators of tourism development strategy according to Suwantoro (2015), namely: promotion, accessibility, tourist areas, types of tourist attractions, tourist products, and human resources. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the management of TWSL has progressed in terms of cleanliness, infrastructure, and environmental education. One of the leading programs, namely